Entre fronteiras e discursos: um estudo comparado sobre o processo de integração física entre Brasil-Guyana e México-Belize - Harris, William John Ebenezer (2016)
This dissertation carries out a comparative analysis of the political processes leading up the construction of two transnational bridges in the Americas; these are the Takutu River Bridge linking Lethem, Region 9, Guyana and Bonfim, Roraima, Brazil; and the Hondo River Bridge linking Santa Elena, Cozoral, Belize and Subteniente López, Quintana Roo, Mexico. In so doing, the study is inserted in a wider body of researches that analyse the process of integration in the Americas through the use of physical infrastructure. The research further highlights how emerging powers use infrastructure as a means of regional power projection in their geopolitical spaces, particularly as it pertains to smaller contiguous neighbours. This analysis takes place in the historical context of countries of the global south and of different colonial traditions, recognising the need to foster integration, and achieve dvancement in this regard through infrastructure. Methodologically, it is an interpretive qualitative study of bibliographical sources and executive speeches, using the comparative method to deduce modes of interaction between two emerging Latin American powers and two relatively small and isolated continental countries of the Anglophone Caribbean. It may be concluded that the two bridges were successfully constructed and inaugurated as part of wider projects for regional integration fostered by Mexico and Brazil for their regions of immediate geopolitical influence, and aided by historically strong bilateral relations in the area of territorial integrity and further, the contemporary transitioning in the search by Caribbean countries for new international partners as old linkages become less viable.